2015
DOI: 10.1044/2015_jslhr-l-14-0344
|View full text |Cite
|
Sign up to set email alerts
|

Designing Caregiver-Implemented Shared-Reading Interventions to Overcome Implementation Barriers

Abstract: Purpose This study presents an application of the theoretical domains framework (TDF; Michie et al., 2005), an integrative framework drawing on behavior-change theories, to speech-language pathology. Methods A multistep procedure was used to identify barriers affecting caregivers' implementation of shared-reading interventions with their children with language impairment (LI). The authors examined caregiver-level data corresponding to implementation iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 47 publications
(67 reference statements)
1
22
0
Order By: Relevance
“…This has very important implications for reading interventions in general. Having established that many reading interventions are not successful (Justice, Logan and Damschroder, 2015;Justice, Skibbe, McGinty, Piasta, & Petrill, 2011), this study suggests that this may be because reading interventions rarely acknowledge the unique nature of family reading practices, and the factors that motivate and discourage parents from reading with their children. This paper has begun to address this issue by ensuring that families, and not the intervention, are at the starting point for this discussion.…”
Section: Conclusion: Implications For Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has very important implications for reading interventions in general. Having established that many reading interventions are not successful (Justice, Logan and Damschroder, 2015;Justice, Skibbe, McGinty, Piasta, & Petrill, 2011), this study suggests that this may be because reading interventions rarely acknowledge the unique nature of family reading practices, and the factors that motivate and discourage parents from reading with their children. This paper has begun to address this issue by ensuring that families, and not the intervention, are at the starting point for this discussion.…”
Section: Conclusion: Implications For Interventionmentioning
confidence: 99%
“…This was explicitly addressed by Justice, Logan and Damschroder (2015) who reported that interventions with caregivers often resulted in fewer sessions being implemented in the home than was recommended, a lack of adequate records detailing the implementation and, in some cases, the implementation of the intervention ceasing altogether (Justice, Skibbe, McGinty, Piasta, & Petrill, 2011;Lonigan & Whitehurst, 1998). This led Justice et al (2015Justice et al ( , p. 1852 to conclude: 'It is most certainly true that implementation of shared reading interventions by caregivers within the home environment does not always reach the levels intended by the intervention developers'.…”
Section: Ijep -International Journal Of Educational Psychology 7(2) 125mentioning
confidence: 99%
“…Reading to and with young children is important because it helps set them up for success in elementary school and beyond (Mol, Bus, & de Jong, ; Sénéchal & LaFevre, ). However, there are many factors that may affect both the quality and quantity of shared reading time at home, including both child characteristics and variables such as parental knowledge, resources, and stress (Bus & van Ijzendoorn, ; Huebner, ; Justice, Logan, & Damschroder, ; Korat, Klein, & Segal‐Drori, ; Neuman, ; Neuman & Celano, ). Moreover, although parents are often advised to engage in shared reading, they are provided with much less information about how to engage in shared reading.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the majority of studies examining these varied approaches to shared reading have focused mainly on child outcomes, which have demonstrated that shared reading has utility for children of varied ages; cultural, linguistic, and economic backgrounds; and both children who are typically developing and those who experience language delays or learning disabilities that affect language development (e.g., Arnold et al, ; Crain‐Thoreson & Dale, ; Huebner & Meltzhoff, ). However, less attention has been paid to how receiving training affects the quality and quantity of parent input during reading time, especially after the training period ends (see Briesch, Chafouleas, Lebel, & Blom‐Hoffman, ; Justice et al, , for more discussion of this topic). Thus, it would be beneficial to better understand what shared reading practices parents use before training and how receiving information about different shared reading strategies and component reading skills affects their use of these practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation